Cardiovascular Disease in Survivors of Adolescent and Young Adult Cancer: A Danish Cohort Study, 1943–2009. (21st May 2014) - Rugbjerg, Kathrine; Mellemkjær, Lene; Boice, John D.; Køber, Lars; Ewertz, Marianne; Olsen, Jørgen H.
Abstract: Background: Cardiovascular disease has emerged as a serious late effect in survivors of adolescent and young adult cancer, but risk has not been quantified comprehensively in a population-based setting. Methods: In the Danish Cancer Registry, we identified 43153 1-year survivors of cancer diagnosed at ages 15 to 39 years (1943–2009) and alive in 1977; from the Danish Civil Registration System, we randomly selected a comparison cohort of the same age and sex. Subjects were linked to the Danish Patient Register, and observed numbers of first hospitalizations for cardiovascular disease ( International Classification of Diseases, Tenth Revision codes I10–I79) were compared with the expected numbers derived from the comparison cohort. We calculated the absolute excess risks attributable to status as a survivor of cancer and standardized hospitalization rate ratios (RRs). All statistical tests were two-sided. Results: During follow-up, 10591 survivors (24.5%) were discharged from the hospital with cardiovascular disease, whereas 8124 were expected (RR = 1.30; 95% confidence interval [CI)] = 1.28 to 1.33; P < .001). The absolute excess risks were 400 and 350 extra cases of cardiovascular disease per 100000 person-years for people aged 20 to 59 and 60 to 79 years at discharge, respectively. Survivors of Hodgkin lymphoma experienced high risks for being hospitalized with valvular disease (RR = 12.2; 95% CI = 9.9 to 15.0; P < .001). Survivors of leukemia had high risks for cerebral hemorrhage (RR = 10.3; 95% CI = 5.5 to 19.1; P < .001) and cardiomyopathy (RR = 8.6; 95% CI = 4.3 to 17.3; P < .001). Conclusions: Survivors of adolescent and young adult cancer are at increased risk for cardiovascular disease throughout life, although each main type of adolescent and young adult cancer had its own risk profile.